A systematic review of social equity in FEWS analyses - Stone, Tiffanie F.; Dickey, Loulou C.; Summers, Haleigh; Thompson, Janette R.; Rehmann, Chris R.; Zimmerman, Emily; Tyndall, John (Frontiers in Environmental Science, 2023)
Integrating social equity considerations into analyses of the food-energy-water systems nexus (FEWS) could improve understanding of how to meet increasing resource demands without impacting social vulnerabilities. Effective integration requires a robust definition of equity and an enhanced understanding of reliable FEWS analysis methods. By exploring how equity has been incorporated into FEWS research in the United States and countries with similar national development, this systematic literature review builds a knowledge base to address a critical research need. Our objectives were to (1) catalog analysis methods and metrics relevant to assessing FEWS equity at varying scales; (2) characterize current studies and interpret shared themes; and (3) identify opportunities for future research and the advancement of equitable FEWS governance. FEWS equity definitions and metrics were categorized by respective system (food, energy, water, overall nexus) and common governance scales (local, regional, national, global). Two central issues were climate change, which increases FEWS risks for vulnerable populations, and sustainable development, which offers a promising framework for integrating equity and FEWS in policy-making contexts. Social equity in FEWS was integrated into studies through affordability, access, and sociocultural elements. This framework could support researchers and practitioners to include equity in FEWS analysis tools based on study scale, purpose, and resource availability. Research gaps identified during the review included a lack of studies effectively integrating all three systems, a need for publicly available datasets, omission of issues related to energy conversion facilities, and opportunities for integration of environmental justice modalities into FEWS research. This paper synthesized how social equity has previously been incorporated into FEWS and outlines pathways for further consideration of equity within nexus studies. Our findings suggested that continued exploration of connections between FEWS, equity, and policy development across scales could reduce social risks and vulnerabilities associated with these systems.